Callus Induction and In vitro Plantlet Regeneration of Gymnema sylvestre R. Br. (Retz.) and the Phytochemical Screening of Natural Plants and Callus Cultures (Plant Tissue Culture and Biotechnology, 2014)
Gymnema sylvestre is a slow growing perennial medicinal woody climber. It belongs to the family Asclepiadaceae. Gymnemic acid, the major bioactive component of this plant species is used as a remedy for type II diabetes. Propagation of this plant is often difficult and expensive. In the present study, in vitro protocols were developed in order to induce callus and regenerate plantlets from different explants of G. sylverstre. As secondary metabolites are important in medicinal plants, studies were carried out to screen phytochemicals present in natural plants and callus. The best medium for callus induction from leaf discs was MS supplemented with 5.0 mg/l 2,4-D. Although, nodal segment grown in MS supplemented with 1.0 mg/l BA gave the highest shoot elongation (14.8 ± 0.20), growth regulator free MS also showed a high elongation of shoots (14.2 ± 0.37) and the difference between those two were non-significant. MS supplemented with 3.0 mg/l IBA was best for root induction. Highest survival percentage (62.5) was observed when plantlets were acclimated in a substrate containing a mixture of soil and sand in the proportion of 1 : 2.  In the present study, phytochemicals present in callus and the leaves of the naturally grown plants were compared using Gas Chromatography- Mass Spectrophotometer. A total of nine compounds was identified from the leaves of naturally grown plants and nine compounds were identified from the callus. Out of all identified phytochemicals, a total of six compounds were present  in both leaves and callus samples suggesting that in addition the plant material, callus may also  be  used as a supplement raw material to obtain secondary metabolites for the pharmaceutical industry. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17521 Plant Tissue Cult. & Biotech. 23(2): 201-210, 2013  (December)